LEVELS OF MONOAMINE OXIDASE ACTIVITES IN CHILDHOOD ACUTE LYMPHOBLASTIC LEUKEMIA AFTER CHEMOTHERAPY - DR. SHATHA ABDUL WADOOD AL- SHAMMAREE; SAHAR ABDUL HAMEED ALI (International Journal of Pharma and Bio Sciences, 2017)
Acute lymphoblastic leukemia (ALL) is the most common type of leukemia in children. The chemotherapeutic agents used in the treatment of ALL may cause many adverse effects on the blood components. The aim of this work is to measure the levels of monoamine oxidase activities (A and B) in ALL patients at first diagnosed stage and after the first course of chemotherapy with (Daunorubicin, Vincristine VRC, L-asparaginase, Cyclophosphamide, Cytosar, Dexon, and Adriamycin). A total of 25 patients with confirmed diagnosis of ALL with mean age 5.3±3.3 years (range 1.2– 12year), and with body mass index (BMI) (range 12.5-19.2) kg/m2 were enrolled. MAO-A and MAO-B activities were determined using colorimetric assay method. White blood cells (WBC) and its differential were assessed using autoanalyzer device. The activity of MAO- A was significantly lower while MAO-B activity was significantly higher after chemotherapy (P<0.05). WBC count, neutrophils %, lymphocyte count, lymphocyte %, monocyte count, and basophils count were significantly lower after chemotherapy (P<0.05) while a non-significant difference in neutrophils, monocyte%, eosinophils %, basophils % was found after chemotherapy. The white blood cells of leukemic children are suppressed after chemotherapy. The increase in MAO –B activity may an indication of oxidative stress increase due to chemotherapy. The decrease of MAO-A activity could be used to predict the outcome of chemotherapy.